Evaluating the influence of wool, cotton and fish on economic growth in Lesotho - Mokhothu-Ramohlanka, Thato (University of the Witwatersrand, Johannesburg, 2021)
This study aims to evaluate the influence of wool, fish, and cotton on the economic growth in Lesotho, analysing a 30-year period from 1990 to 2020. The paper provides an analysis of the long-term and short-term relationships between wool, cotton, fish and economic growth, and their causal effects on economic growth. The study used the Augmented Dickey-Fuller and the Phillips Perron unit root tests to determine whether the data set is stationary. The Johansen co-integration model identified the existence of long-run relationships. The error correction model and the Granger causality test determined the short run and causal relationships, respectively. Findings indicate that wool and cotton have a positive and significant influence on economic growth. In contrast, fish has a negative influence both in the long and short run. In addition, the study found unidirectional causation between economic growth and wool exports, bidirectional causality between cotton exports and economic growth, and unidirectional causation between economic growth and fish exports. Finally, to improve the benefits of the agricultural sector in Lesotho, there is a need for policy reform around structural changes to diversify exports and exports markets
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2021
Keywords: Wool; Fish; Cotton; Lesotho; Economic growth; UCTD; SDG-8: Decent work and economic growth